Perbandingan Kadar Kolesterol pada Guru Obes dan Non-Obes di SMP Negeri I dan II Kauditan Minahasa Utara - Rumampuk, Hizkia; Doda, Diana V.D.; Polii, Hedison (Universitas Sam Ratulangi, 2017)
Abstract: To date, obesity incidence is increasing globally in developing and developed countries. Increased prevalence of obesity suggests that there is an increased risk of obesity-related illnesses. Metabolic and lipid transport disorders can lead to hypercholesterolemia. This can happen especially among people with less physical activity, such as teacher. This study was aimed to assess the comparison of cholesterol levels in obese and non-obese teachers. This was an analytical descriptive study with a cross-sectional design. Respondents were 35 teachers at SMP Negeri I and II (junior high school) Kauditan Kabupaten Minahasa Utara consisting of 26 females and 9 males. Body mass index (BMI) was calculated and fasting cholesterol levels were checked from peripheral blood using autocheck tool. The results showed that there were 16 (45.7%) non-obese respondents and 19 (54.3%) obese respondents. Of the 35 respondents, 24 (68.6%) had normal cholesterol levels and 11 (31.4%) had hypercholesterolemia. The bivariate analysis using Mann Whitney test revealed that there was no significant difference in cholesterol levels between obese and non-obese teachers (P = 0.537). Conclusion: There was no significant difference in cholesterol levels between obese and non-obese teachers at SMP Negeri I and II Kauditan Kabupaten Minahasa Utara.Keywords: cholesterol level, BMl, teachersÂ Abstrak: Insiden obesitas dilaporkan tetap mengalami peningkatan secara global, baik di negara berkembang maupun negara maju. Peningkatan prevalensi obesitas ini memberikan informasi bahwa terdapat peningkatan risiko penyakit yang terkait obesitas. Gangguan metabolism dan transportasi lipid bisa mengakibatkan hiperkolesterolemia. Hal ini bisa terjadi pada orang yang kurang aktif secara fisik, antara lain guru. Penelitian ini bertujuan untuk membandingkan kadar kolesterol guru yang obes dan tidak obes. Jenis penelitian ialah deskriptif analitik dengan desain potong lintang. Responden ialah 35 orang guru di SMP Negeri I dan II Kauditan Kabupaten Minahasa Utara, terdiri dari 26 perempuan dan 9 laki-laki. Indeks masa tubuh (IMT) dihitung dan kadar kolesterol puasa diperiksa dari darah perifer menggunakan alat autocheck. Analisis bivariat menggunakan Mann Whitney dengan nilai signifikan P â‰¤ 0,05. Hasil penelitian mendapatkan 16 (45,7%) responden non-obes dan 19 (54,3%) responden obes. Kadar kolesterol normal pada 24 (68,6%) responden dan hiper-kolesterolemia pada 11 (31,4%) responden. Anilisis bivariat menggunakan uji Mann Whitney menunjukkan tidak terdapat perbedaan bermakna pada kadar kolesterol antara guru obes dan non-obes (P=0,537). Simpulan: Tidak terdapat perbedaan bermakna pada kadar kolesterol antara guru obes dan non-obes di SMP Negeri I dan II Kauditan Kabupaten Minahasa Utara.Kata kunci: kadar kolesterol, IMT, guru